2019
DOI: 10.5812/pedinfect.64109
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Theory-Based Education on the Promotion of Preventive Behavior Among Mothers, Concerning the Self-Medication for Children

Abstract: Self-medication is one of the basic problems in the health system of Iran. The purpose of the present study is to determine the effect of theory-based education on the promotion of preventive behavior among mothers, concerning the self-medication for children. This study is an educational randomized controlled trial research that was designed and implemented for the first time in Iran. The samples consisted of 112 mothers with children under age six who referred to health centers of AzadShahr (a city in the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…One of the findings of this study is that mothers' knowledge should be promoted to prevent toddlers' home accidents in the experimental group. This findings is in line with another study conducted in Iran, in which the knowledge of mothers with below six-year-old child improved after using the TPB with the aim of preventing self-medication (17). In a similar study, the TPB had effects on students' knowledge regarding prevention of road traffic injuries (18).…”
Section: Discussionsupporting
confidence: 89%
“…One of the findings of this study is that mothers' knowledge should be promoted to prevent toddlers' home accidents in the experimental group. This findings is in line with another study conducted in Iran, in which the knowledge of mothers with below six-year-old child improved after using the TPB with the aim of preventing self-medication (17). In a similar study, the TPB had effects on students' knowledge regarding prevention of road traffic injuries (18).…”
Section: Discussionsupporting
confidence: 89%
“…[ 16 ] Education for mothers of children under age six can improve their knowledge and attitudes and increase their understanding and can also improve practices related to the lack of self-medication for their children. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in line with another study conducted in Iran, in which the awareness of mothers with children below 6 years improved after using TPB with the aim of preventing selfmedication. 36 In a similar study, TPB had effects on students' awareness regarding prevention of road traffic injuries. 31 A study in Brazil showed that an expository and dialogued educational intervention increased mothers' awareness about falling, drowning, and intoxication prevention among children.…”
Section: Discussionmentioning
confidence: 92%